VD_FINDINFO Décision / 2013 / 49 vom 15. November 2012 - VD Tribunal cantonal (2012)
FRAIS DE LA PROCÉDURE, CLASSEMENT DE LA PROCÉDURE, PRÉSOMPTION D'INNOCENCE | 395 let. b CPP (CH), 426 al. 2 CPP (CH)